Model Penanaman Nilai Karakter Pada Masyarakat Perspektif Ilmu Pendidikan Islam - Qur'ani Nurhakim, Haditsa; Isnan Rojibillah; Aan Hasanah; Bambang Samsul Arifin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The instillation of values and character is one of the efforts in forming a civilized, dignified, and high-integrity society. In the context of civilization development, these values are not only instilled through formal education, but also through various integrated social, cultural, and political channels. This study aims to examine in depth various methods of instilling values applied in society through government institutions, social institutions, public spaces, and mass media from the perspective of Islamic Education. This approach was chosen to critically examine the relevance and contribution of Islamic values in shaping the social character of modern society. The method used is a qualitative-descriptive approach through library research, by reviewing various relevant literature from both classical and contemporary sources. The results of the study indicate that the methods of role models, habituation, providing advice (mau'idzah), and constructive dialogue have proven effective in shaping community character when implemented consistently, collectively, and sustainably by formal and non-formal institutions. The instillation of values will be more meaningful when integrated holistically into the national education system and social development programs. This study recommends the importance of synergy between the government, religious leaders, educators, and the mass media in designing strategies for instilling values that are contextual, adaptive, and based on the principles of Islam rahmatan lil 'alamin in order to create a strong and inclusive civil society